Pengaruh PDRB Sektoral Terhadap Pendapatan Asli Daerah (PAD) Kabupaten/Kota di Kalimantan Barat - B01108103, ALDINO MUSKARI (Jurnal Pembangunan dan Pemerataan, 2012)
This study aims to analyze and verify the effect of GDRP accretion sector (primary, secondary, tertiary) to increase the Own Regional Revenue (PAD) District/Town in West Kalimantan. This study using the a descriptive method to decrypt the result from the research and using the causality method for decrypt the relation between independent variable (primary sector, secondary, and tertiary) to the dependent variable (PAD). The analysis tool used is the multiple regressions by using the panel data which combining between the time series data for five years (2007-2011) with cross section data of 12 districts/cities in West Kalimantan, the resulting processed data of 60 observations (5 years x 12districts/cities) using a data processing programs Eviews 6. From the analysis result of constant value (C) of -42.765, which means that if the Primary Sector, Secondary, and Tertiary is not remain or unchanged, then district/city PAD in West Kalimantan will decrease about 42.75%. Based on the regression result, on the Primary sector obtained t value is less than t table that is 1.714727 < 2.000 with the probability in the amount of 0.0933 is bigger than 0.05 (, which means that the primary sector take a possession that is not significant to the PAD. Furthermore, on the secondary sector obtainable from t arithmetic is bigger than t table that is 2.068933 > 2.000 with probability in the amount of 0.0443 less than 0.05 (, which means that the secondary sector have a significant effect to the PAD. Then the tertiary sector obtained by t arithmetic is bigger than t table that is 5.34789 > 2.000 by probability in the amount 0.0000 less than 0.04 (, which means that the tertiary sector have a significant effect to the PAD. Based on the test of result of the coefficient determination (R2) indicated the value amount of 0.945269.Its means the amount of leverage that given by primary, secondary, tertiary sector to the district/cities PAD in West Kalimantan at once is 94,53%, while the leftover is amount 5.47% is influenced by the other factor which is not investigate in this research for example inflations, investment, per capita income, employed population, and the others factors. Further research is needed to determine others variables that affect the warfare of districts/cities society in Province West Kalimantan.